INVESTIGATING THE PERFORMANCE OF BRIDGES EQUIPPED WITH ELASTOMERIC BEARINGS REINFORCED WITH FIBRE UNDER TRAFFIC AND SEISMIC LOADS - Arian AGHELFARD; Mohammad Sadegh ROHANIMANESH; Ali VATANSHENAS (Scientific Journal of Silesian University of Technology. Series Transport)
The seismic elastomeric bearings reinforced with fibre is considered as a new technology in comparison to other conventional isolator systems in civil engineering. In this type of bearing, recycled fibres replaced traditional steel plates used in common bearings. Therefore, this type of bearing has been studied in recent years due to both environmental and cost-saving advantages. The shortage of references about the application of this type of bearing in the bridge industry, and particularly the continuous-span bridges, prompted the researchers in this study to investigate the performance of the isolated reinforced concrete box girder bridges with continuous spans. Reducing the acceleration transmission from the substructure to the superstructure is one of the main advantages of using seismic bearings. Based on the study of the structural models, it was found that, in most cases, elastomeric bearings reinforced with fibres showed a suitable performance and reduced the acceleration applied to the superstructure by absorbing the earthquake energy.